VISUAL COMMUNICATIONS AS THE BASIS OF AN EFFECTIVE ADVERTISING MESSAGE - Vladyslav Vlasov (Інтегровані комунікації, 2025)
The article explores visual communications as a foundation for creating effective advertising messages within the modern information environment. The relevance of the topic stems from the adaptation of visual communication in advertising and design to the current socio-economic conditions in Ukraine and globally. The development and integration of new visual communication trends in advertising campaigns — both commercial and governmental — not only complement or transform the perception of textual messages but also create new associations for target audiences, evoking emotions and influencing consumer behavior. The aim of the study is to analyze the use of visual communication in brand advertising messages. The visual advertising of Ukrainian brands and military identity was examined through comparative analysis and content analysis. The research also considers the potential of AI, which opens up new opportunities for personalized and trend driven advertising messages.